Empowering the community on legal protection in e-commerce transactions - Nur Insani; Arpin Jumadi; Haritsa Haritsa; Rahmawati Rahmawati; Yudin Yunus (University of Merdeka Malang, 2023)
The implementation of a community service program sponsored by the Legal Aid Institution of Ichsan University Gorontalo. The initiative took place at the office of the sub-district head in Dulalowo Village, Central City District, Gorontalo City, where the community faced challenges in comprehending the legal regulations governing electronic transactions (e-commerce). This lack of awareness often led to disputes and losses between businesses and consumers. The program aimed to empower the community through the empowering the community on legal protection in electronic transactions (e-commerce) program. A combination of surveys, questionnaires, lectures, and discussions was employed to achieve the desired outcomes. The results of this community service initiative demonstrated a noteworthy improvement in the participants' understanding of legal norms and juridical foundations concerning electronic transactions (e-commerce). As a result, the community became more discerning and cautious when engaging in online transactions, now equipped with knowledge about safe and secure strategies for conducting such transactions. The positive impact of this endeavor contributes to a more informed and confident community in Gorontalo City, fostering a thriving e-commerce environment for both businesses and consumers alike